2012
DOI: 10.1371/journal.pone.0030626
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Disease-Induced Host Responses in Bovine Tuberculosis and the Identification of Potential Diagnostic Biomarkers

Abstract: Bovine tuberculosis (bTb) remains a major and economically important disease of livestock. Improved ante-mortem diagnostic tools would help to underpin novel control strategies. The definition of biomarkers correlating with disease progression could have impact on the rational design of novel diagnostic approaches for bTb. We have used a murine bTb model to identify promising candidates in the host transcriptome post-infection. RNA from in vitro-stimulated splenocytes and lung cells from BALB/c mice infected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 53 publications
9
56
2
Order By: Relevance
“…CXCL10, also known as IFN-g-induced protein-10 (IP-10), is a chemokine detected within human and bovine tuberculoid lymph node granulomas (Ferrero et al, 2003;Aranday-Cortes et al, 2012a). Produced by monocytes, it attracts activated T cells and monocytes to granulomas and promotes a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CXCL10, also known as IFN-g-induced protein-10 (IP-10), is a chemokine detected within human and bovine tuberculoid lymph node granulomas (Ferrero et al, 2003;Aranday-Cortes et al, 2012a). Produced by monocytes, it attracts activated T cells and monocytes to granulomas and promotes a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…More targeted investigations have examined tissues or organs containing tuberculoid granulomas, focusing on regions within or near lesions (Widdison et al, 2006(Widdison et al, , 2009Shu et al, 2014). Others have focused on the granuloma itself, through the use of immunohistochemistry (IHC) or laser capture microdissection (LCM) combined with real time quantitative polymerase chain reaction (qPCR) (Palmer et al, 1999;Wangoo et al, 2005;Johnson et al, 2006Johnson et al, , 2007Aranday-Cortes et al, 2012a). Relatively few studies have focused on granulomas of different stages of development (Palmer et al, 1999;Johnson et al, 2007;ArandayCortes et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPD-specific IL-17 mRNA responses at 60 and 90 days after experimental M. bovis infection correlated with the presence of gross tuberculous lesions at necropsy 4 months after challenge (7). Using laser capture microdissection followed by qPCR, Aranday-Cortes et al demonstrated increased IL-17A and IL-22 expression within tuberculous granulomas versus nonaffected tissues from experimentally infected cattle, particularly in more advanced lesions (50). In the present study, M. bovis infection also elicited IL-17A protein responses that correlated with infection, similar to IFN-␥ responses (Table 5).…”
Section: Figmentioning
confidence: 99%